Kennedy speaks in an Open Dialogue in the College Union (1971)
Kennedy held an Open Dialogue with students and faculty of the university located in the newly opened College Union, later called the University Union. The matters of the discussion regarded tenure of faculty, the dorm's open door policies, increases in foreign student tuition, and more.